EFFECT OF PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR-ALPHA-AGONISTS ON DIABETES-INDUCED ACUTE KIDNEY INJURY: ROLE OF OXIDATIVE STRESS AND HYPERLIPIDEMIA - Chakkarwar, Vishal Arvind; Kawtikwar, Pravin (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study investigated the possible effect of fenofibrate and gemfibrozil peroxisome proliferator-activated receptor-alpha agonist in diabetes-induced acute kidney injury (AKI) in rats. Methods: Rats were administered streptozotocin (STZ) (50 mg/kg, i.p., single dose) to induce experimental diabetes mellitus. The development of diabetic AKI was assessed biochemically and histologically. In addition, the diabetes-induced lipid profile and renal oxidative stress were assessed. The single dose of STZ produced diabetes, which induced renal oxidative stress, altered the lipid profile and subsequently produced kidney injuryAKI in 7 weeks by increasing serum creatinine, blood urea nitrogen (BUN), proteinuria, and glomerular damage. Treatment with fenofibrate and gemfibrozil (30 mg/kg p.o, 7 weeks) normalized the altered lipid profile by decreasing serum cholesterol, triglycerides, and increasing serum high-density lipoprotein in diabetic rats. Lisinopril (1 mg/kg, p.o., 7 weeks, reference compound) prevents lipid alteration and development of diabetic AKI. Result: Fenofibrate and gemfibrozil, besides hyperglycemia, significantly prevented the development of diabetic AKI by reducing (serum and tissue) oxidative stress, hyperlipidemia, serum BUN, creatinine, and urinary protein. Further, fenofibrate, but not gemfibrozil, considerably reduced renal structural and functional abnormalities in diabetic rats. The fenofibrate was more effective in attenuating the diabetes-induced AKI and renal oxidative stress as compared to treatment with and gemfibrozil. Conclusion: The fenofibrate and gemfibrozil treatment markedly prevented the diabetes-induced AKI. In comparison, the fenofibrate is found to be a superior approach to attenuate the diabetic AKI than gemfibrozil.